2008
DOI: 10.1080/08860220802134607
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neutrophil Gelatinase-Associated Lipocalin as a Marker of Renal Function in Non-Diabetic Patients with Stage 2–4 Chronic Kidney Disease

Abstract: The current Kidney Disease Outcomes Quality Initiative (K/DOQI) guidelines advocate creatinine-based equations for estimating GFR to identify patients with potential kidney disease and classify them into different stages due to the fact that serum creatinine is very insensitive to changes in the glomerular filtration rate. Very few biomarkers exist for monitoring chronic kidney disease. The aim of the study was to assess whether NGAL could represent a novel, sensitive marker of kidney function in adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 10 publications
7
57
1
Order By: Relevance
“…In the present study the higher NGAL level, and the correlations between NGAL and other kidney parameters were studied (results and fig. 1-6) and are in agreement with many reports, which implies that NGAL is an early indicator biomarker for both RT and advanced CKD patients and can be used to start early treatment in these patients [39][40][41][42]. Malyszko et al in their study showed that in patients with delayed graft function; there was no fall in serum NGAL or cystatin-c.…”
Section: Resultssupporting
confidence: 78%
“…In the present study the higher NGAL level, and the correlations between NGAL and other kidney parameters were studied (results and fig. 1-6) and are in agreement with many reports, which implies that NGAL is an early indicator biomarker for both RT and advanced CKD patients and can be used to start early treatment in these patients [39][40][41][42]. Malyszko et al in their study showed that in patients with delayed graft function; there was no fall in serum NGAL or cystatin-c.…”
Section: Resultssupporting
confidence: 78%
“…It was further postulated that sNGAL and urine NGAL (uNGAL) may be useful as sensitive markers of kidney impairment/injury in CKD patients. 15 …”
Section: Introductionmentioning
confidence: 99%
“…We also found additional univariate correlations (serum creatinine, urea, urea reduction ratio, and also with other markers of inflammation). As demonstrated previously, NGAL correlated with kidney function in kidney allograft recipients and patients with chronic kidney disease [29,30]. Therefore, the presence or absence of residual renal function may affect NGAL levels significantly.…”
Section: Discussionmentioning
confidence: 74%